Studies on the Cytotoxic Activities of Punica granatum L. var. spinosa (Apple Punice) Extract on Prostate Cell Line by Induction of Apoptosis. (17th December 2012) - Sineh Sepehr, Koushan; Baradaran, Behzad; Mazandarani, Masoumeh; Khori, Vahid; Shahneh, Fatemeh Zare
Abstract : The Punica granatum L. var. granatum (pomegranate) has been demonstrated to exert antitumor effects on various types of cancer cells. The present study aimed to evaluate the medicinal herbs Punica granatum L. var. spinosa (apple punice) that are native to Iran. This study was determined to test the possible cytotoxic activity and induction of apoptosis on human prostate cell lines. The effect of ethanol extracts of the herbs on the inhibition of cell proliferation was assessed by MTT colorimetric assay. PC3 cell lines treated with the extracts were analyzed for the induction of apoptosis by cell death detection (ELISA) and TUNEL assay. Dye exclusion analysis was performed for viability rate. Our results demonstrated that the Punica granatum L. var. spinosa extract dose dependently suppressed the proliferation of PC3 cells (IC50 = 250.21 μ g/mL) when compared with a chemotherapeutic anticancer drug (Toxol) (Vesper Pharmaceuticals) with increased nucleosome production from apoptotic cells. The Punica granatum L. var. spinosa extract attenuated the human prostate cell proliferation in vitro possibly by inducing apoptosis. The Punica granatum L. var. spinosa is likely to be valuable for the treatment of some forms of human prostate cell line.